Fonction sexuelle masculine et sexualité féminine - Giami, Alain (Communications, 2007)
Major changes have occurred in male and female sexual function/dysfunction research and treatments. Male erectile dysfunction has been re-conceptualized as an organic dysfunction, which marks a dramatic shift from previous conceptions of psychogenic impotence developed during the 60' and the 70's. This shift is based on major scientific discoveries, and pharmacological advances that took place since the early 80's under the influence of North American urologists. The release of sildenafil in 1998 was thecorner stone of a new paradigm of treatments focusing on male penile activity, far remote from any psychological approaches. More recently, the same group of urologists started to reconsider Female Sexual Dysfunction using the same organic/biological model of sexual function. New pharmaceutical products are currently under trial for the treatment of this new category of female sexual disorder. But as opposed to the absence of public adverse reaction to the development of this approach of male function, many voices raised to oppose this new conception of female function. A major discussion took place in the British Medical Journal (2003) stating that female sexual function was not organically driven, but rather determined by the social, psychological and interpersonal context of female sexual activity and relations. One of the major dimension of this discussion opposed the so-called "simplicity" of male sexual function to the "complexity" of female sexual function.
Number: 1 Publisher: Persée - Portail des revues scientifiques en SHS
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 2000 à aujourd'hui; 2000-2009; angleterre; approches et analyses; cours; discipline; essentialisme; europe; féminisme radical; patriarcat; premier cycle; pédagogie; périodes historiques; recherche; régions géographiques; santé; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Homosexualités: variations régionales - Julien, Danielle; Lévy, Joseph J. (Presses de l'Université du Québec, 2007)
Les études sur l'homosexualité ont, à ce jour, essentiellement porté sur les milieux urbains, négligeant les autres milieux de vie comme les petites villes et les régions rurales, où les conditions socioculturelles peuvent contribuer à amplifier les difficultés de dévoilement et d'expression publique de l'identité ou des préférences sexuelles. La rareté ou l'absence de réseaux associatifs ou de rencontres et la carence de ressources d'aide dans le domaine de la santé et des services sociaux pourraient aussi contribuer à l'isolement ainsi qu'aux sentiments d'aliénation et de malaise chez ces personnes. Afin de mieux cerner ces enjeux, les auteurs analysent les réalités quotidiennes, sociales, relationnelles et sexuelles de lesbiennes et gais vivant en région. Ils explorent les dimensions touchant la famille et l'homoparentalité, ainsi que les variations dans les usages grâce à Internet et à l'intervention en ligne. Ces réflexions pourront sans doute aider à mieux comprendre les réalités des personnes homosexuelles vivant à l'extérieur des grands centres et, ainsi, orienter des interventions psychosociales plus adaptées chez ces populations encore négligées.
Section: xiii, 268 pages : illustrations ; 23 cm
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; hétérosexisme; identités LGBTQIA2+; premier cycle; pédagogie; périodes historiques; queer; québec; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques